Indicators for the monitoring of central counterparties in the EU - Emanuel Alfranseder; Paweł Fiedor; Sarah Lapschies; Lucia Orszaghova; Paweł Sobolewski (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2018)
This ESRB Occasional Paper complements the publication of indicators on central counterparties (CCPs) in the ESRB's Risk Dashboard as part of its monitoring framework. It provides a methodological background to the development of the individual measures and discusses different aspects that should be considered when designing a monitoring framework for CCPs. The paper also highlights a number of areas in which more granular data are required in order, for example, to monitor the interconnectedness of CCPs within the broader financial system.CCPs play a key role in financial markets, as they reduce counterparty credit risk. This role is now heightened following post-crisis reforms of the over-the-counter (OTC) derivatives markets. Since CCPs may be viewed as systemically important institutions, it is crucial to ensure that they are regulated and monitored effectively. The ESRB has, therefore, sought to strengthen the framework used to analyse developments at CCPs in the EU from a macroprudential perspective.Each monitoring framework relies on the availability of suitable data. It is therefore positive that CCPs publish data on a quarterly basis under the CPMI-IOSCO public quantitative disclosure framework. These data provide a rich source of information covering several aspects of CCPs' functioning and are the basis of the indicators the ESRB has developed to analyse developments in central clearing in the EU.The indicators are designed to provide a macroprudential view over time of CCPs' resources, liquidity and collateral policies, margin and haircut requirements, interoperability arrangements as well as market structure and concentration at CCP level. The indicators cover all CCPs that are authorised within the EU, although the values of individual measures across CCPs should be analysed and interpreted with caution, bearing in mind that there are significant differences between individual CCPs' business models, membership structures and products cleared.
Keywords: G10; G18; G23; G28; 330; central counterparties; monitoring; PQD data; systemic risk